Pengaruh Lingkungan Kerja Dan Disiplin Terhadap Motivasi Kerja Pegawai Kecamatan Kembangbahu - Ramadhani, Dhea Fitri; Kuswanto (CV ODIS, 2024)
A company is a tool for a company to achieve its goal, which is to make a profit by selling goods and services to the public. To achieve the company's goals, employees must be motivated to work with passion. The purpose of the study is to determine the influence of the work environment and work discipline on the work motivation of employees in Kembangbahu District. The research sample is all from the employee population in the research results of Kembangbahu sub-district with a total of 34 employees. With the results showing that the work environment has no contribution to motivation. Meanwhile, work discipline has a significant influence on motivation.